Are game-based mobile applications effective for young children’s informal learning in a science museum? - Nicolaidou, Iolie; Vasquez Christodoulou, Marlen; Tourapi, Christiana; Aristeidis, Loizos (My University, 2023)
Schoolchildren can benefit from interactive, engaging learning experiences when they visit museums. Previous studies attempted to engage and educate children in museum visits using technologically supported ways such as mobile devices and apps (Ha et al., 2021), augmented reality (Moorhouse et al., 2019), virtual reality (Fouad & Elsaid, 2021) and gamification (Weng et al., 2019). Recent studies began to explore the impact of gamified mobile apps on user experience and informal learning (Ha et al., 2021). Gamification can be an effective method for museums to interact with their visitors. However, studies on the gamification of museum experiences are scant (Çeti̇n & Erbay, 2021). To address research gaps identified in the literature and increase our knowledge of effective and engaging ways to support children’s learning through gamification, we designed a theoretically-grounded, game-based educational application addressed to young children who are visitors to a science museum, focusing on water, in a European city. The game is available in the Greek language, it is accessible via mobile devices (http://game.wbl.com.cy/), and it was designed to address the needs of 4th-6th year primary school students (ages 10 and older). Students are transported back in time to solve a mystery in 1937 when the city temporarily lost access to clean drinking water. Children are encouraged to look closely at museum exhibits to solve the mystery using an inquiry-learning approach, within 45 minutes. They navigate in four stations on a virtual map in non-linear navigation and receive points and badges when correctly answering questions associated with the four exhibits. The study aimed to evaluate the effectiveness of the game-based application as an intervention to support students’ learning of concepts associated with preserving water quality. The research question was: Are game-based mobile applications for young children’s informal learning in a museum setting effective? A one-shot pre-test post-test case study was used. Participants were twenty 2nd graders (M=8.05 years old, SD=0.498) from a public primary school. Data sources included a test, consisting of 10 multiple-choice questions focusing on museum exhibits, which was embedded in the game. Each correct answer received one point. The test was administered before and after students’ interaction with the game. Results showed that students’ learning increased from Mpre=3.55 (SD=1.62) to Mpost=6.00 (SD=2.00) after they visited the museum. A paired samples t-test showed that this change was statistically significant (t17=-4.768; p<.001). The study was conducted with an age group younger than the intended age group of students for which the application was designed. Younger children faced several challenges, the most important of which was a disparity between their reading level and the reading level required to understand the text within the game. For this age group, the guidance of knowledgeable adults was necessary for children to interact with the technology. Despite challenges, a comparison of students’ pre-test and post-test scores revealed significant learning gains, which is a positive finding indicating the effectiveness of the game-based application that was designed, even for students younger than its expected target audience. The application is expected to help museum educators, teachers, and families to facilitate children’s learning in the context of this museum.
Keywords: Gamification; Science museum; Children; Informal learning; Mobile devices; Applications